A Review of the Role of Occupational Therapy in Managing Patients with Acute Kidney Injury - Negi, Neha; Abhilash Dung Dung (Gayaku Publisher, 2024)
Acute Kidney Injury (AKI) is a critical condition that significantly impacts both the physical and psychological well-being of patients, often leading to extended hospital stays and increased healthcare costs. This review explores the role of Occupational Therapy (OT) in managing AKI patients, particularly in enhancing functional outcomes and psychological health. The review synthesizes findings from 21 peer-reviewed studies published between 2019 and 2024, focusing on OT interventions for adult AKI patients. Results indicate that OT improves functional independence, as measured by ADL assessments, and enhances psychosocial outcomes by reducing anxiety and boosting self-management skills. Additionally, OT's role in interdisciplinary team approaches is highlighted, improving communication and individualized care. Despite the promising findings, the review also identifies limitations, such as small sample sizes and varying intervention methods. The paper concludes by advocating for more large-scale studies to establish evidence-based protocols for OT in AKI rehabilitation.